أهمية مهارة القراءة في فهم الكتب العربية - Al Fatih Al Fatih (UIN Fatmawati Sukarno Bengkulu, 2019)
Reading is the process of pronouncing secret or aloud writing symbols and understanding what it contains and what it reads. The objectives in this article are to define the importance of writing skill in understanding Arabic books. The results in this article are that reading skill is very important in understanding Arabic books. It contains the concept of reading, reading objectives, types of teaching the skill of reading, and the method of language game by means of ripped papers.